The placental barrier of Kerodon rupestris (Rodentia: caviidae) - Moacir Franco de Oliveira; Gleidson Benevides de Oliveira; Ferdinando Vinícius Fernandes Bezerra; Felipe Venceslau Câmara; Alexsandra Fernandes Pereira; Alexandre Rodrigues Silva; Maria Angélica Miglino (Bioscience Journal, 2016)
The placenta of the rodents generally has a chorial-allantoic, discoid and hemochorial shape. Since they resemble the process of human placentation, such characteristics make this order an interesting experimental model for understanding placentation, placental barrier and the physiological mechanisms involved in maternal-fetal exchanges. Due to the fact that Kerodon rupestris may be used as placental model, current analysis characterizes the rodentÂ´s placental barrier ultrastructure. Current assay used three and two placentas, obtained from the Centro de Multiplicação de Animais Silvestres da Universidade Federal Rural do Semi-Ãrido (CEMAS/UFERSA) in Mossoró RN Brazil, respectively at the mid-third period of pregnancy and at the final third period of pregnancy. Samples, measuring approximately 1.0 cm, were collected and fixed in paraformaldehyde solution in a phosphate buffer 0.1 M, pH 7.4, at 4°C, while 0.5 mm2 fragments were fixed in glutaraldehyde solution 2.5%, buffered with sodium phosphate at 0.1 M, pH 7.4, and analyzed, respectively, under light and electron transmission microscope. The Kerodon rupestrisÂ´s placenta had a discoid form and resulted from the interaction between the chorion and the allantois. It was thus classified as a model chorioallantoic placenta which, macro and microscopically, consisted of lobes predominantly made up of fetal capillaries that interposed mostly in gaps or maternal spaces. The inter-hematic space or maternal-fetal barrier placenta of K. rupestris is composed of three distinct elements represented by the fetal capillary wall, basement membrane and a single layer of trophoblast cells of a syncytial nature or strictly syncytiotrophoblast, which separate maternal from fetal blood, and at the same time is the medium through which all metabolic exchange between mother and fetus are processed. These characteristics are typical of hemochorial placentas. Since the barrier contains a single syncytiotrophoblast layer, it is classified within the hemomonochorial subtype, a behavior similar to that reported in hystricomorph rodents such as the agouti, paca, capybara and cavy.